ANALISIS POLA ASUH ORANG TUA TERHADAP ANAK YANG KECANDUAN GADGET ( STUDI KASUS DI KELURAHAN GUNDALING I KECAMATAN BERASTAGI KABUPATEN KARO) - Vinka Dwi Hayati (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
The family is the first school for children, through the children's parents will be taught various things. The active role of parents is needed in maintaining and educating their children, especially when their children are included in early childhood, namely the age of 0-8 years or often referred to as the golden age . There are three types of parenting styles, namely permissive parenting, liberal parenting and democratic parenting. This study aims to describe parenting patterns for children who are addicted to gadgets in Gundaling I Village, Berastagi District, Karo Regency. The main informants in this study were 4 parents of children who often play gadgets at Warung Kopi Isu. The key informants in this study were the owners of Warung Kopi Isu, as well as additional informants, namely neighbors and teachers of the main informant's children. This research method is descriptive qualitative with life story case studies. Data were collected through literature study, observation, interviews and documentation. The results of this study show how parenting is done by parents in dealing with their children who are addicted to gadgets.